Effects of Mental Practice in Novice Learners in a Serial Positioning Skill Acquisition. Issue 2 (October 2014) - Gomes, Thábata V. B.; Ugrinowitsch, Herbert; Marinho, Nádia; Shea, John B.; Raisbeck, Louisa D.; Benda, Rodolfo N.
The effects of mental practice in novices were investigated. University students ( N = 60) performed a serial aiming task, distributed in 5 groups of 12: mental practice, physical practice, mental-physical practice (first mental then physical practice), physical-mental practice (first physical then mental practice), and a control group that only performed the tests. Participants transported three tennis balls among six containers in a pre-established sequence in a target time. In the acquisition phase and retention test (24 hr. later), the task was the same; in the transfer test, 5 min. after the acquisition phase, sequence and time changed. Six trials were performed in the acquisition phase, and each test consisted of 9 trials. The performance measures were absolute error, constant error, and variable error; a t test and a two-way ANOVA were used to compare the acquisition phase and tests, respectively. Physical practice and both groups of combined conditions presented better performance in tests than the mental practice and control groups. Mental practice without motor experience in the task did not improve motor learning. Prior physical performance is desirable before conducting mental practice.